2011
DOI: 10.3109/0886022x.2011.559675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Therapeutic Efficacy of Epoetin Beta and Epoetin Alfa in Maintenance Phase Hemodialysis Patients

Abstract: In May 2009 for financial reasons, the epoetin product used for hemoglobin (Hb) maintenance in our renal dialysis unit was changed from epoetin beta to epoetin alfa. Although widely believed that the dosage requirements are the same, we undertook a retrospective analysis to investigate whether the dosage requirements in chronic renal failure patients were comparable for both preparations. We studied 128 stable end-stage renal failure patients on hemodialysis (three times per week) receiving erythropoietin ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
6
0
4
Order By: Relevance
“…However, doses of the agents administrated in the present study were different from above mentioned study. Additionally Loughnanm et al did not detect any statistically significant differences between erythropoietin Erythropoietin alfa versus erythropoietin beta alpha and beta in the case of increasing hemoglobin levels (11). However, in the case of needed dose they concluded that a lower dose of beta erythropoietin is needed to achieve the same hemoglobin level.…”
Section: Discussionmentioning
confidence: 95%
“…However, doses of the agents administrated in the present study were different from above mentioned study. Additionally Loughnanm et al did not detect any statistically significant differences between erythropoietin Erythropoietin alfa versus erythropoietin beta alpha and beta in the case of increasing hemoglobin levels (11). However, in the case of needed dose they concluded that a lower dose of beta erythropoietin is needed to achieve the same hemoglobin level.…”
Section: Discussionmentioning
confidence: 95%
“…In another study, Loughnan et al [8] compared the efficacy and safety of epoetin beta and epoetin alfa in the maintenance phase of hemodialysis patients. Their results indicated that higher doses of epoetin alfa are required to maintain Hb in the target level.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that elimination half-life of epoetin beta is longer than epoetin alfa, which is probably due to different glycosylation. As a result, lower doses may be needed to maintain hemoglobin and hematocrit in the target level [7][8][9]. However, the Kidney Disease Improving Global Outcomes (KDIGO) guideline along with other evidence suggest that epoetin alfa and beta have the same efficacy and require the same dose to be administered to patients with CKD-induced anemia [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Àâòîðû ïîêàçàëè, ÷òî ïðè âíóòðèâåííîé èíúåêöèè ó ýïîýòèíà-b íà 20 % áîëüøå, ÷åì ó ýïîýòèíà-a, ïåðèîä ïîëóâûâåäåíèÿ, ïðè ïîäêîaeíîì ââåäåíèè ýïîýòèí-b âñàñûâàåòñÿ ìåäëåííåå, ÷åì ýïîýòèí-a, è ðåòèêóëîöèòàðíûé îòâåò â ïåðèôåðè÷åñêîé êðîâè ÿð÷å âûðàaeåí ïðè èñïîëüçîâàíèè ýïîýòèíà-b [11]. Ïðè ïðèìåíåíèè ðÝÏÎ-a è ðÝÏÎ-b ó áîëüíûõ òåðìèíàëüíîé ñòàäèåé ïî÷å÷íîé íåäîñòàòî÷íîñòè, íàõîäÿùèõñÿ íà ãåìîäèàëèçå, èññëåäîâàòåëÿìè èç Áðóìôèëäñêîãî ãîñïèòàëÿ (×åëìñôîðä, Âåëèêîáðèòàíèÿ) áûëî ïîêàçàíî, ÷òî äëÿ ïîääåðaeàíèÿ êîëè÷åñòâà ãåìîãëîáèíà íà óðîâíå 110 -125 ã/ë íåîáõîäèìû áîëåå âûñîêèå äîçû ðÝÏÎ-a [12]. Îäíàêî â äðóãîì èññëåäîâàíèè, ïðîâåäåííîì â àíàëîãè÷íîé ãðóïïå ïàöèåíòîâ â Öåíòðå çäîðîâüÿ ã. Òóçëà (Áîñíèÿ è Ãåðöåãîâèíà), áûëè ïîëó÷åíû äàííûå î òîì, ÷òî íåò äîñòîâåðíûõ ðàçëè÷èé â êëèíè÷åñêîì ýôôåêòå ðÝÏÎ-a èëè ðÝÏÎ-b, è ïóòü ââåäåíèÿ ïðåïàðàòîâ (ïîäêîaeíûé èëè âíóòðèâåííûé) íå âëèÿåò íà ðåçóëüòàò [13].…”
Section: ðåçóëüòàòû è èõ îáñóAeäåíèåunclassified